2020
DOI: 10.1111/trf.15699
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of labeling red cell units with minor antigen historical results and process considerations

Abstract: BACKGROUND Several approaches are used by blood centers when providing minor (non‐ABO/D) antigen‐negative RBCs to hospitals. Details vary but include providing results on the unit labeling intended for clinical use without retyping or providing results on packing documents or via computer query requiring confirmation. Recent regulatory changes allow labeling with historical minor antigen results, defined as previously performed by the donor center on two different donations with results linked to the donor and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…We demonstrated that neither of the frequent synonymous SNVs c.588A>G and c.810G>A lead to altered JK antigen expression. Moreover, we were able to exclude disruption of proper transcript splicing caused by c.810A as previously suspected [17,18]. Similarly, all samples carrying allele JK*01N.20 showed normal JK:1 expression.…”
Section: Discordance In the Description Of Alleles -Consequences For ...supporting
confidence: 70%
See 1 more Smart Citation
“…We demonstrated that neither of the frequent synonymous SNVs c.588A>G and c.810G>A lead to altered JK antigen expression. Moreover, we were able to exclude disruption of proper transcript splicing caused by c.810A as previously suspected [17,18]. Similarly, all samples carrying allele JK*01N.20 showed normal JK:1 expression.…”
Section: Discordance In the Description Of Alleles -Consequences For ...supporting
confidence: 70%
“…Taking this into account, null alleles were present 25 times, including JK*01N.09, 01N. 18 The null allele JK*02N.01.588A_G was present only in Southeast Asians (Philippines, Thailand, and Vietnam). In addition, one Filipino was homozygous for this allele.…”
Section: Allele Frequencies In Various Blood Donor Panelsmentioning
confidence: 99%
“…We confirm this hypothesis by investigating donor exposures in a patient who presented with anti‐C in the plasma after receiving 38 C– units: 12 from Black or Hispanic donors and 26 from Caucasian. RH genotyping of donors from the preceding 6 months ruled out rare alleles encoding weak C expression that can be missed by serologic typing 6 . Rather, anti‐C was associated with transfusion of RBCs from a Black donor with a rare hr B – phenotype and heterozygous for two variant RHD and two variant RHCE*ce .…”
Section: Discussionmentioning
confidence: 96%
“…RH genotyping of donors from the preceding 6 months ruled out rare alleles encoding weak C expression that can be missed by serologic typing. 6 Rather, anti-C was associated with transfusion of RBCs from a Black donor with a rare hr Bphenotype and heterozygous for two variant RHD and two variant RHCE*ce. In addition to a C-phenotype, the RBCs were DAK+ and V/VS+; however, antibody identification was consistent with anti-C although the presence of additional anti-V/VS and anti-DAK could not be excluded.…”
Section: Discussionmentioning
confidence: 98%